#### Answer

(-1, -3)

#### Work Step by Step

Write the first equation as a solution for x in terms of y:
7x - 3y = 2
7x = 3y + 2
x = $\frac{3}{7}y + \frac{2}{7}$
Substitute x in the second equation with the equation in terms of y and solve for y:
6($\frac{3}{7}y + \frac{2}{7}$) + 5y = -21
$\frac{18}{7}y + \frac{12}{7}$ + 5y = -21
$\frac{53}{7}y = -\frac{159}{7}$
y = -3
Let y = -3 in the first equation to solve for x:
x = ($\frac{3}{7})(-3) + \frac{2}{7}$
x = -1
Check the solution (-1, -3) in the second equation:
6(-1) + 5(-3) = -21
-6 - 15 = -21
-21 = -21; True